High burden of wasting among children under-five with hydrocephalus receiving care at CURE children’s hospital in Uganda: a cross-sectional study - Naula Grace; Edith Mbabazi; David Mukunya; Josephine Tumuhamye; Humphrey Okechi; Emmanuel Wegoye; Peter Olupot-Olupot; Joseph KB Matovu; Leah Hopp; Agnes Napyo (BMC Nutrition, 2024)
Abstract Background Hydrocephalus is one of the most common neurological disabilities presenting in children. Although there are limited studies on its association with wasting, neurological comorbidities such as dysphagia have been associated with an increased risk of wasting in children. In this study, we aimed to determine the prevalence and factors associated with wasting in children less than five years with hydrocephalus. Methods We conducted a cross-sectional study at various satellite clinics of CURE Children’s Hospital in Uganda between September and November 2021. Children with hydrocephalus were identified at the outpatient departments of the satellite clinics of the Cure Children’s Hospital and these include Mbale, Gulu, Lira, Jinja and Katalemwa. A structured questionnaire was used to collect information on several variables including (1) for the mother: socio-demographic characteristics, partner support, and wealth index (2) for the child: socio-demographic characteristics, clinical symptoms, feeding difficulties and neural comorbidity. Anthropometric measurements were also taken and these included the mid-upper arm circumference. Data were analysed using Stata version 14. We estimated adjusted odds ratios and their corresponding 95% confidence intervals while relying on multivariable logistic regression models. Results The prevalence of wasting among children with hydrocephalus was 23.2% (n = 89/384) (95%CI: 19 − 27.7%). Their mean age was 19.5 months (SD 16.8). Most of the children were below 12 months (47.9%) and were male (57.5%). The factors associated with wasting among children with hydrocephalus included: having; difficulty in chewing and swallowing (AOR = 2.6, (95%CI:1.05–3.94), a poor appetite (AOR = 1.74, (95%CI: 1.31–2.32), difficulty in breathing (AOR = 1.9, (95%CI: 1.18–3.16), chocking on food (AOR = 1.42, (95%CI:1.1–1.9) and attending the Mbale satellite clinic (AOR = 2.1 (95% CI 1.19–3.7). Children under 5 years of age with hydrocephalus that were born to women whose highest level of education was 7 to 10 years of formal schooling (AOR = 0.32, 95%CI: (0.12–0.87) were less likely to be wasted. Conclusions and recommendations The prevalence of wasting among children with hydrocephalus was high. The factors associated with wasting were mainly feeding challenges. We recommend that children with hydrocephalus should be given greater attention regarding their nutrition especially those with various forms of feeding difficulties. The caregivers of children with hydrocephalus should receive counseling on nutrition and on the best modalities to rely on while feeding their children.